Do the Photos Tell it All? Representing Torture in the Images from Abu Ghraib - Dauenhauer, Katrin (Current Objectives of Postgraduate American Studies, 2012)
In 2004, pictures of U.S. military personnel abusing detainees of the Abu Ghraib prison came to public attention, triggering a new debate on torture. This essay examines the shock potential of the photographs from Abu Ghraib as well as the representability of pain. It argues that the role of photography in the Abu Ghraib torture scandal is a complex and complicated one, oscillating between becoming complicit in the torture and exposing it.